At the outer edge of STEMI time: even after 12 hours, the clock keeps ticking. (3rd October 2022) - Martinho, M; Cale, R; Nabais, S; Briosa, A; Pereira, E; Pereira, A R; Grade Santos, J; Ferreira, B; Santos Cunha, D; Santos, P; Vitorino, S; Eusebio, C; et al.
Abstract: Introduction: Although primary percutaneous coronary intervention (pPCI) is not a class I recommendation in all patients (pts) presenting within 12 to 48h of symptom onset (late ST-segment Elevation Myocardial Infarction, STEMI), there is increasing evidence supporting its routine use in this population. Data on long-term clinical outcomes is sparse. Objective: To evaluate long-term MACE in late-STEMI pts submitted to pPCI and compare with clinical outcomes of early reperfusion groups. Methods: Retrospective analysis of consecutive pts submitted to pPCI due to STEMI between 2010 and 2015 in a pPCI centre. Included pts were stratified in 5 groups according to symptom-to-balloon time (SBT): <3h; 3–6h; 6–12h; 12–24h; 24–48h. Of a total of 903 pts, 19 pts were excluded due to SBT >48h. Long-term events were established as 5y mortality and 5y-MACE (a composite endpoint of death, re-infarction, heart failure hospital admission and ischemic stroke). The cumulative incidence of long-term outcomes was calculated by the Cox regression analysis and presented according to the Kaplan-Meier method. Results: Of the 884 pts included in the study, stratification according to SBT was: pPCI<3h (47.4%), pPCI 3–6h (24.9%), pPCI 6–12h (16.5%), pPCI 12–24h (8.0%), and pPCI 24–48h (3.2%). These groups showed no significant difference in terms of demographic characteristics (age, CV risk factors, previous coronary disease or heart failure), clinical severity (systolic arterial pressure, Killip-Kimball class, left ventricle ejection fraction) and angiography findings (multivessel disease, complete revascularization and PCI success). After a median follow-up of 76 (56; 98) months, 5-year mortality was 20.6% (182 pts) and 5-year MACE was 23.3% (206 pts). MACE was associated with increased median SBT: 5.0 (2.0; 9.0) hours vs 4.0 (2.0; 6.5) hours, p<0.001. Of the MACE components, the only that showed a significant association with higher median SBT was mortality: 5.0 (2.0; 10.0) hours vs 4.0 (2.0; 6.0), p<0.001. Differences in long-term outcomes were significant when considering SBT stratified by revascularization time (Figure 1). Conclusions: As expected, there is a clinical benefit of early reperfusion for long-term cardiovascular events. Within the late-STEMI group, there seems to be a clear distinction between pPCI<24h and >24h, although the clinical benefit of pPCI timing most probably acts a continuum. Funding Acknowledgement: Type of funding sources: None.